O papel dos ecossistemas de carbono azul no contexto da emergência climática: o caso do manguezal do parque nacional de Jericoacoara - Vasconcelos, Mirella Ribeiro Parente de (2024)
The ocean and its coastal zones are essential to the planet's climate balance due to their ecosystem services of carbon absorption. The carbon stored, sequestered and released by the coastal and marine ecosystems of mangroves, angiosperms and marshes is called Blue Carbon. However, due to climate change and the degradation of these regions, their CO2 absorption capacity is being compromised, contributing to the acidification of the ocean, the rise in mean sea level and the intensification of natural events such as storms and coastal erosion. It is therefore necessary to keep the ocean healthy, one of the ways of assuring that is through the preservation and restoration of Blue Carbon ecosystems. Thus, the general objective of this research was to identify the role of Blue Carbon ecosystems in the context of the climate emergency and how to enable the conservation and restoration of these ecosystems, especially mangroves, from international premises to local actions. The focus on the local level is the analysis of the Gestão Compartilhada do Parque Nacional de Jericoacoara National Park. To this end, the main international commitments were presented in order to demonstrate the legal treatment given to these Blue Carbon ecosystems. By relating them to the Nationally Determined Contributions (NDCs) presented by the member countries of the Paris Agreement, it was possible to see an increase, between the first and second review cycles, in solutions based on the nature of Blue Carbon ecosystems as measures to mitigate and/or adapt to climate change. The research revealed that the latest Brazilian NDC presented needs updating to increase its level of ambition. Therefore, the possibility of including measures focused on Blue Carbon ecosystems in the scope of the Brazilian NDC was presented, especially regarding mangroves due to their potential in Brazilian territory, as found in the Parque Nacional de Jericoacoara (PNJ). The conservation and restoration of the mangroves in this conservation unit should therefore be seen as one of the main objectives of the PNJ Acordo de Gestão Compartilhada to be pursued by the environmental co-management partnership signed between the State of Ceará, the Federal Government and ICMBio. The articulation of the Projeto Universidade Azul to strengthen community-based tourism with a focus on the Mangrove Ecological Walk, promoted by residents of the communities surrounding the PNJ, is an action provided for in the agreement that should be implemented to help preserve and sustainably use the mangrove swamp. It was possible to conclude that this articulation, by contemplating the blue carbon ecosystem, becomes an interesting action for updating the Brazilian NDC and consequently for tackling climate change, aiming at the health of the ocean and its coastal zones.